Knowledge Improvement After Dental Health Education for Elementary School Students in Surabaya, East Java - Sitalaksmi, Ratri Maya; Kresnoadi, Utari; Mundiratri, Karina; Utami, Farasty; Ashrin, Meinar Nur (Faculty of Dental Medicine Universitas Airlangga, 2023)
Background: During the coronavirus disease-19 (COVID-19) pandemic, many people were afraid to go to the dentist, which affected their dental and oral health conditions. Dental cavities may hamper children's growth and development; if this condition continues, it will affect the children's dietary intake, which may impact their quality of life and, if allowed to, cause stunting. Although in this condition, we still have to take preventive precautions with dental health education in school-age children. This required increasing dental health knowledge and understanding of dental disorders, particularly. Purpose: To describe oral and dental health knowledge improved following dental health education at Muhammadiyah 4 Elementary School, which is located in Pucang, Surabaya City, East Java. Methods: Two surveyors were responsible for data collecting. This study's sample size was 105 people ranging from third to fifth grade. The seminar covered dental and oral health via a hybrid method. The participants were asked to fill out a questionnaire form for the pre-and post-test to determine the improvement of oral and dental health knowledge for the dental health education evaluation. Results: Most oral and dental health participants understood the presentation on oral and dental health education. The post-test percentage was higher (89.14%) than the pre-test rate (60.29%). Conclusion: The program findings demonstrated that oral and dental health education with a hybrid method effectively increased elementary school children's understanding of dental and oral health status.